Optimizing Food and Beverage Business with an Omnichannel System in Emerging Markets (ASEAN) - Ipahriani Rahman; Buyung Romadhoni; Andi Mappatompo Badawi; Andi Ifayani Haanurat; Muchriady Muchran (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze strategies for optimizing food and beverage businesses through omnichannel systems in increasingly competitive ASEAN emerging markets. Specifically, the study explores effective omnichannel implementation patterns, identifies success and failure factors in channel integration, examines the strategic implications of omnichannel adoption, and investigates the development of omnichannel systems in emerging market countries. This research employed a qualitative approach using a descriptive research design. Data were collected through passive participant observation, in-depth interviews, and documentation. A purposive sampling technique was applied to select ten key informants representing large-scale brands and MSMEs from Indonesia and Malaysia, including Gacoan, Fore Coffee, Kopi Kenangan, Tsuka Ramen & Bento, Es Teler Pattiro, Yappay, Kopi Komar, Lazuna Chicken, Moka Kopi, and Sugarbun. The data were analyzed using descriptive qualitative analysis involving data collection, reduction, display, and conclusion drawing, while credibility was ensured through source and technique triangulation. The findings reveal that the most effective omnichannel model for food and beverage businesses is the consistent integration of physical stores with digital channels, including social media, WhatsApp, marketplaces, delivery applications, and digital point-of-sale systems. The success of omnichannel implementation is influenced by information consistency, service responsiveness, stock accuracy, and standardized operating procedures, whereas the primary barriers include weak system integration, network limitations, unsynchronized inventory, and inadequate employee readiness. Furthermore, omnichannel implementation improves operational efficiency, expands market reach, enhances customer satisfaction, and strengthens customer loyalty. The study also indicates that emerging markets are increasingly moving toward integrated and data-driven digital ecosystems, although technological maturity varies across countries. The findings imply that food and beverage MSMEs should gradually strengthen digital integration by adopting simple technologies such as WhatsApp Business, QRIS, social media platforms, and digital POS systems before implementing more advanced features. Policymakers and supporting institutions are encouraged to provide digital training and infrastructure support to accelerate omnichannel transformation among MSMEs in emerging markets. Future studies may employ quantitative approaches to examine the effects of omnichannel implementation on business performance, customer satisfaction, and loyalty.